The Bohun and Lancaster lordships in Wales in the fourteenth and early fifteenth centuries - Davies, RR (1965)
The present thesis is a study of three of the greater marcher lordships of mediaeval Wales - Monmouth, Cydweli and Brecon, as well as of smaller units, both within and outside the marches, which were administratively attached to them - Ogmore, Caldicot and a few manors in Herefordshire and Gloucestershire, These lordships were part of the landed inheritances of two of the greatest fanilies of later mediaeval England - the house of Bohun (until its failure in the male line in 1273) and the house of Lancaster, and it is on the relatively abundant records of these families, supplemented wherever possible by other non-seignorial sources, that the study is based. It is essentially a study in three dimensions. Continued in thesis ...